Determination and Quantification of Phenytoin in Human Plasma by Liquid Chromatography with Electrospray Ionization Tandem Mass Spectrometry. Issue 1 (2008) - Roy, S. M. N.; Yetal, S. M.; Vaidya, V. V.; Joshi, S. S.
Abstract : A rapid and simple high pressure liquid chromatography method with mass spectrometry detection was developed and validated for the determination of phenytoin in human plasma. Metaxalone was used as internal standard. The sample preparation involves a rapid and simple procedure based on liquid-liquid extraction. Analysis was performed in less than 3.0 minutes in isocratic mode on a reversed phase C18 column (5μ; 50 × 4.6 mm) using a mobile phase composed of acetonitrile-buffer 2 mM ammonium acetate (80:20 v/v ), pH of buffer adjusted to 3.4 using formic acid, at 0.4 mL min-1 flow rate. The calibration curves were linear in the measured range between 101.2 ng mL -1 and 5060.0 ng mL -1 . The validated lowest limit of quantification was 101.2 ng mL -1 for phenytoin. The mean relative recovery for drug and Internal standard was found to be 78.33% and 77.04%, respectively. The described method has the advantage of being rapid and easy and it could be applied in therapeutic monitoring of these drugs in human plasma.